KETAKSAMAAN HERMITE-HADAMARD TERHADAP INTEGRAL RIEMANN-STIELTJES - Denny Ivanal Hakim; Hendra Gunawan (Jurnal Ilmiah Matematika dan Pendidikan Matematika (JMP), 2012)
The Hermite-Hadamard inequality is an inequality for convex functions that gives an estimate for the integral mean value of a convex function on a closed interval by its value at the middle of interval and the average of its values at the endpoints. The Hermite-Hadamard inequality can be generalized by using the Riemann-Stieltjes integral mean value. An application of the Hermite-Hadamard inequality with respect to Riemann-Stieltjes integral for estimating the power mean of positive real numbers by the aritmethic mean is given at the end of discussion.